(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
This study raises the problem of the construction of identity in parentified adolescent. It is indeed a question of measuring the influence of this wide spread phenomenon in the far north region of Cameroon, on the identity process as a major developmental task in adolescence. To achieve this, a qualitative study was conducted with 10 adolescents from the city of Maroua. Based on a semi-directive interview guide and a parentification rating scale, informations focusing on the two main themes of the study was collected, analyzed and discussed. It emerges that in a situation of parentification, the identity process is disturbed, the crisis of adolescence and existential questions give way to adult concerns for which the subject is not prepared. The quest for masculine or feminine identity is short-circuited, it gives way to a precocious tendency that is unsuitable for carrying out adult tasks.